PERAN WORK LIFE BALANCE DAN PENGHARGAAN TERHADAP KETERHUBUNGAN SOSIAL DAN KOMITMEN ORGANISASI KARYAWAN GENERASI Z DI BEKASI - Ayuningrum, Priandini Fadhillah; Pranitasari, Diah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to identify the extent to which Work-Life Balance (X1) and rewards (X2) affect organizational commitment (Y2) with social connectedness (Y1) functioning as a mediating variable. The method used in this study is quantitative. In this study, the population of generation Z workers in Bekasi City based on the Bekasi City Central Statistics Agency was 446,992 workers. The researcher chose snowball sampling in determining the sample. The number of samples in this study was 400 respondents. The method that will be used by the researcher is quantitative data analysis. This method presents data in the form of numbers and emphasizes objective research results through descriptive statistical analysis. To manage the data, the researcher will utilize computer software, namely SmartPLS version 4. SmartPLS version 4 is used to calculate statistical values, conduct construct validity and reliability tests (AVE, Composite Reliability, Outer Loadings), and test structural models (path coefficient, R-square, and Q-square). The results of the study showed that Work-Life Balance has an effect on Organizational Commitment, Rewards have an effect on Organizational Commitment, Work-Life Balance has an effect on Social Connectedness, Rewards have an effect on Social Connectedness, Social Connectedness has an effect on Organizational Commitment, Social Connectedness can indirectly mediate the effect of Work-Life Balance on Organizational Commitment, Social Connectedness can indirectly mediate the effect of Rewards on Organizational Commitment.